2003
DOI: 10.1046/j.1468-2982.2003.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Headache in an English District

Abstract: Headache prevalence, characteristics and impact in adults were measured using a cross-sectional general population survey in North Staffordshire, UK. A postal survey was mailed out to 4885 adults (aged > or = 18 years) with an adjusted response rate of 56% (n = 2662). Of respondents 93% reported headache ever and 70% in the last 3 months. Women and younger people reported higher headache prevalences. Of those reporting headache in the last 3 months, 23% experienced headache at least weekly and 16% experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 27 publications
8
96
1
3
Order By: Relevance
“…Details of the baseline survey have been reported elsewhere [1] . In brief, a random sample of 5,000 adults aged 18 years and over was selected from the practice registers of fi ve general practices in North Staffordshire, UK, 1,000 from each practice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the baseline survey have been reported elsewhere [1] . In brief, a random sample of 5,000 adults aged 18 years and over was selected from the practice registers of fi ve general practices in North Staffordshire, UK, 1,000 from each practice.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we reported on the prevalence of headache in the adult general population, and noted that it declined at older ages [1] . This fi nding parallels reports of a wide number of other pain conditions declining in frequency with age [2,3] , but the size of the decline was greater than reported for other painful conditions such as back pain [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that women have more frequent, longer lasting, and more severe headaches than men [15] although some studies show that Pain intensity and attack frequency tend to be similar in men and women [16].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…For example in the field of pain research, numerous population-based surveys suggest that taking part in research is strongly linked to both age and gender (Walsh, 1994;Papageorgiou et al, 1995;Jinks et al, 2002;Boardman et al, 2003). Authors who examine non-response more closely have reported that response is also related to such things as social class (Tickle et al, 1996;Hill et al, 1997) and health status; in a population-based survey of the prevalence of low back pain, responders to the survey were found to have a higher consultation rate for back pain in the year subsequent to the survey t han those who did not respond (7.1% cf.…”
Section: Generalizability Of Study Findingsmentioning
confidence: 99%